EAT-PAD: Educating about psychiatric advance directives in India. (May 2019) - Philip, Sharad; Chandran, Dhanya; Stezin, Albert; Viswanathaiah, Geetha C; Gowda, Guru S; Moirangthem, Sydney; Kumar, Channaveerachari Naveen; Math, Suresh Bada
Background: With India enacting the Mental Health Care Act (MHCA; No. 10 of 2017a), Psychiatric Advance Directives (PADs) have been legalised and have become binding orders for psychiatrists treating patients. There is a paucity of research into acceptability of PADs in Indian mental health care, likely due to a lack of awareness. There are no educational measures about PADs provided for in this Act. Facilitators and facilitation methods have not been elaborated upon as well. Aim: The aim of this study is (a) to develop/evaluate the effectiveness of a structured Education-cum-Assessment Tool (EAT) in providing information regarding PADs and (b) to evaluate modes of facilitation required by patients to complete PADs. Methods: A tool was developed as per provisions regarding PADs in the Mental Health Care Bill of 2013. This tool was administered to patients ( n = 100), purposively sampled from the adult psychiatry review out-patient department (OPD). Patients were evaluated on retention of information, completion of PADs, modes of facilitation and time taken to write one. Results: Mean years of education was 8.28 (±5.74) years and mean duration of illness was 8.30 (±7.04) years. In all, 65% had Below-Poverty Line (BPL) status. All participants completed valid PADs in an average of 15 minutes. About 93% required facilitation via assistance in writing and reminding. The mean EAT scores implied above 70% retention but did not relate to types of facilitation. Conclusions: EAT scores can be used as an approximate measure of the patient's ability to understand and retain information which is a part of decisional capacity. Types of facilitation can help in understanding patient's ability to communicate their choices. Service providers may find EAT a time-effective tool for uniformly educating service users regarding PADs and indirectly assessing competence.